Mindfulness and Meditation at University 10 Years of the Munich Model - de Bruin, Andreas (Achtsamkeit - Bildung - Medien, 2021)
Why should mindfulness and meditation be taught at universities? What impact could the establishment of such programs have on students and on the education system itself? Andreas de Bruin showcases the remarkable results of the first ten years of the Munich Model »Mindfulness and Meditation in a University Context« - a program started in the year 2010 in which 2000 students have already participated. Through meditation-journal entries featured in the book, students describe the effects of mindfulness and meditation on their studies and in their daily lives. In addition to an overview of cutting-edge research into mindfulness and meditation, along with in-depth analyses and explanations of key terms, the book also contains numerous practical exercises with instructions.